Remote sensing and mathematical modelling of Lake Vostok, East Antarctica: past, present and future research - Popov, S. V. (2024)
The paper presents a review of the studies carried out in the area of the subglacial Lake Vostok (East Antarctica) to date. They include geophysical, glaciological, geodesic, and geological investigations. The most important geophysical investigations were carried out by the Polar Marine Geosurvey Expedition. They included reflection and refraction seismic, and also radio-echo sounding. The major contribution to the study of this region was made by American researchers, who in the 2000/01 field season performed a complex airborne geophysical survey on a regular network. Their work included magnetometric, gravimetric, and radio-echo sounding measurements. All the research conducted found that the water surface area is 15790 km2, and its altitudinal height changes from -600 to -150 m. The average depth of Lake Vostok is 400 m, and the maximum marks reach 1200 m. The water body volume is estimated at 6 100 km3. There are 11 islands in the lake, and their total area is 365 km2. In addition, 56 isolated subglacial water bodies were found around the lake. A special section is devoted to a review of mathematical models of heat and mass transfer processes in the glacier and water movement in Lake Vostok.